DNA damage protecting and free radical scavenging properties of Terminalia arjuna bark in PC-12 cells and plasmid DNA - Kumar, G. Phani; Navya, K.; Ramya, E.M.; Venkataramana, M.; Anand, T.; Anilakumar, K.R. (Free Radicals and Antioxidants)
Objective: Terminalia arjuna is commonly known as Arjuna and widely used as cardioprotective agent in Indian traditional medicine. The present study was undertaken to evaluate the protective effect of ethanolic extract of T. arjuna bark (TAA) and its fractions, including dichloromethane (TAD), ethyl acetate (TAE), butanol (TAB) and water (TAW) against free radicals, protein oxidation and DNA damage. Methods: Protective effect of arjuna bark against H2O2 induced DNA damage on pBR322 plasmid and rat adrenal PC-12 cells was analyzed by DNA strand breakage assay and single cell gel electrophoresis (Comet assay) respectively. AAPH induced protein oxidation was analyzed with SDS-PAGE. In vitro antioxidant activities were carried out by spectrophotometric methods to asses free radical scavenging activities, such as DPPH, hydroxyl, ABTS, nitric oxide, metal chelation, FRAP and reducing power. Results: The ethanolic extract and its fractions of arjuna bark effectively protected H2O2 induced DNA damage and AAPH induced protein oxidation in the following manner: TAE > TAB > TAA > TAD > TAW. The maximum inhibition of DPPH, hydroxyl, ABTS, nitric oxide radicals and metal chelation was observed in TAE fraction (IC50 values: 270 2 mg/ml, 175 11 mg/ml, 25 1.2 mg/ml, 405 9 mg/ml, 310 11 mg/ ml, 82 4 mg/ml, respectively). Conclusion: In the present study we report that arjuna bark extracts ameliorate various impairments associated with DNA damage and free radical formation.
Keywords: DNA damage protection; PC-12 cells; Antioxidant activity; Free radical scavenging activity; Terminalia arjuna